E-procurement implementation challenges during the COVID-19 pandemic / Ronn Rowell Roangis@Rojis … [et al.] - Roangis@Rojis, Ronn Rowell; Mohamad Bohari, Asmah Alia; Zulkifi, Mohd Zul Aswad; Sebri, Nur Izzati; Mahat, Noorsaidi (UiTM Press, 2023)
E-procurement, one of the Malaysian government's activities under its e-Government application, represents a more sustainable endeavour that uses the internet as the platform for its transactions. E-procurement was intended to improve the current manual procurement method used in government organisations. However, the support from industry, particularly the construction industry, remains far ahead. At the beginning of 2020, a new virus known as COVID-19 spread globally to affect communities worldwide. As of June 2021, more than 180 million instances of this virus variant had been identified. The pandemic caused by the COVID-19 virus has significantly impacted the construction sector, having prompted modest shifts in project timelines and corking approaches. Internet-based applications are being utilised and every stakeholder is being urged to adopt e-based methods. This research identifies the challenges faced by contractors using e-procurement applications during the COVID-19 pandemic. A questionnaire was distributed to contractors based in Kota Kinabalu, Sabah. This research will specifically help to explore e-procurement practices in Sabah.